I can prove 1 = 2

\(\boxed{\text{Step1}}\) Lets say **y = x**

\(\boxed{\text{Step2}}\). Multiply by x **xy = \(x^2\)**

\(\boxed{\text{Step3}}\) Subtract \(y^2\) from each side **xy - \(y^2\) = \(x^2\) - \(y^2\)**

\(\boxed{\text{Step4}}\) Factorize each side **y(x-y) = (x+y)(x-y)**

\(\boxed{\text{Step5}}\) Divide both sides by (x-y) **y = x+y**

\(\boxed{\text{Step6}}\) Since x = y **y = y + y**

\(\boxed{\text{Step7}}\) And so... **y = 2y**

\(\boxed{\text{Step8}}\)Divide both the sides by y \(\boxed{\text{1 = 2}}\)

Which step is wrong?

×

Problem Loading...

Note Loading...

Set Loading...